Lesotho : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Lesotho's Poverty Reduction Strategy Paper (PRSP) Progress Report for the period between January and December 2002. The achievements demonstrate that the government of Lesotho has reaffirmed its commitment to a highly participatory approach and process of preparing a community-driven and country-owned national strategy to fight poverty. The effort to measure poverty at the national level, through the National Human Development Index and the Core Welfare Indicator Survey dovetailed with the Household Budget Survey, is progressing well with completion of the latter foreseen by May 2003.